Determinants of communication dynamics on doctor-patient interactions: a descriptive cross-sectional investigation - Narayanan Namboothiri G; Ajith V; Herma Fathima; Hiba Saleem K T; Hibah Moideen Hakim; Hina C; Hisham Aboobacker (Global Journal of Medicine and Public Health)
Introduction: Communication dynamics in doctor-patient relationships are vital for improving patient outcomes,